Upstream proton cyclotron waves at Venus near solar maximum. Issue 1 (22nd January 2015) - Delva, M.; Bertucci, C.; Volwerk, M.; Lundin, R.; Mazelle, C.; Romanelli, N.
Abstract Long‐term magnetometer data of Venus Express are analyzed for the occurrence of waves at the proton cyclotron frequency in the spacecraft frame in the upstream region of Venus, for conditions of rising solar activity. The data of two Venus years up to the time of highest sunspot number so far (1 Mar 2011 to 31 May 2012) are studied to reveal the properties of the waves and the interplanetary magnetic field (IMF) conditions under which they are observed. In general, waves generated by newborn protons from exospheric hydrogen are observed under quasi‐ (anti)parallel conditions of the IMF and the solar wind velocity, as is expected from theoretical models. The present study near solar maximum finds significantly more waves than a previous study for solar minimum, with an asymmetry in the wave occurrence, i.e., mainly under antiparallel conditions. The plasma data from the Analyzer of Space Plasmas and Energetic Atoms instrument aboard Venus Express enable analysis of the background solar wind conditions. The prevalence of waves for IMF in direction toward the Sun is related to the stronger southward tilt of the heliospheric current sheet for the rising phase of Solar Cycle 24, i.e., the "bashful ballerina" is responsible for asymmetric background solar wind conditions. The increase of the number of wave occurrences may be explained by a significant increase in the relative density of planetary protons with respect to the solar wind background. An exceptionally low solar wind proton density is observed during the rising phase of Solar Cycle 24. At the same time, higher EUV increases the ionization in the Venus exosphere, resulting in higher supply of energy from a higher number of newborn protons to the wave. We conclude that in addition to quasi‐ (anti)parallel conditions of the IMF and the solar wind velocity direction, the higher relative density of Venus exospheric protons with respect to the background solar wind proton density is the key parameter for the higher number of observable proton cyclotron waves near solar maximum.